Comparison of the Toxicity of Watermelon Rind Extract (Citrullus lanatus) and Melon Rind Extract Using BSLT Method - Fajrin Noviyanto Fajrin; Rinditya Lutfiah Syafa Kurnadi; Eva Kholifah; Afifah Nur Shobah; Leni Halimatusyadiah (Sam Ratulangi University, 2024)
Toxicity analysis is a preliminary test to observe a toxic pharmacological activity to find a safe dose to be developed into a new drug. The plants that potentially have poisonous effects are Watermelon rind (Citrullus lanatus) and Melon rind (Cucumis melo). The purpose of this study was determine the toxic potential of watermelon rind and melon rind using Brine Shrimp Lethality Test. Test BSLT and phytochemical screening. The results of research on watermelon rind and melon rind contain secondary metabolites, amely alkaloids, flavonoids, tannins, saponins. The result of the BSLT test watermelon rind extract and melon rind extract were different. For watermelon rind extract, the LC50 value was 305,19 µg/ml and for melon rind extract, the LC50 value was 816,73 µg/ml. The LC50 value pbtained from the research results of the two samplees is toxic to Artemia salina Leach, because the LC50 value is < 1000 µg/ml. Statistical test results using One Way Anova obtained a significant value of 0.027 where there were significant differences in the two samplesand various concertration, but both plants had the same toxic effect on Artemia salina Leach larvae. Keywords: Citrullus lanatus; Cucumis melo; LC50; toxicity